خبر الواحد إذا خالف سد الذرائع عند المالكیة دراسة تأصیلیة تطبیقیة ج - ببوش, محمد العربي (University of Eloued-جامعة الوادي, 2016)
This study aims at answering the the following question: Can “ahaad hadeeths” be accepted by the Maalikis if it is contradictory to Sasadd al-dharaa’i (blocking the means)? In the first chapter, this conceptual and applied study focus on how Malikis see these two terms: “ahaad hadeeths” and “blocking the means”. So we should find the definition and the justification of “ahaad hadeeths” then if ever it leads to certitude or to an incertitude and when it can be accepted. Then a definition is given to Sasadd al-dharaa’i (blocking the means), its evidences, parts and conditions. We confirm if the Maalikis are characterized by Sasadd al-dharaa’i (blocking the means)? The second chapter (theapplied part) collects the matters where the Maalikis go against the “ahaad hadeeths” outside according to the rule of Sasadd aldharaa’i (blocking the means). These matters were chosen from different “fiqh” books. They clarify the Malikis position about “ahaad hadeeths” that go against their rules. The most important result of this study is that Maalikis go against the “ahaad hadeeth” outside in order to prohibit what may lead to committing sins according to a religious justification. Finally, this study recommends a just path based on shar‘i texts that respects the “Maqasid” and the reality facts.
مذكرة ماستر
Keywords: خبر الواحد / سد الذرائع / المالكية; The news of the one / blocking the excuses / the Malikis